Utilisation and perception of complementary alternative therapies among pregnant lady in Terengganu: a pilot of preliminary study - Ain Widad, Abdullah; Wee, B.S.; Rosliza, Yahaya; Marhazlina, Mohamad; Mohd Razif, Shahril; Lua, P.L. (2020)
Complementary and alternative therapies were termed as a group of various medical and healthcare practices and products that are not currently considered to be part of conventional therapy. There were increasing demands of complementary and alternative therapies worldwide for different type of purposes. With the aim of identifying the general existing trend in the utilization and perception of complementary and alternative therapies (CATs) among pregnant women in Terengganu, this cross-sectional study used structured questionnaires consist of sociodemographic characteristics, utilisation and perception of complementary alternative therapies (UPCATS) that was modified according to the study and pilot tested among healthy pregnant women, who were recruited from two selected health clinics in Terengganu. A total of 18 pregnant women aged 22-38 years completed the survey. Majority of them utilised CATs in their third trimester (83.3%, n=15). Among the participants, 77.8% (n=14) used CATs to prevent illness or reduce pain (n=12, 66.7%) and also for supplementation (n=6, 32.3%). Half of the participants obtained information regarding CATs from nurses. They were unlikely to surf to information of CATs from web (n=3, 16.7%). In conclusion, pregnant women in Terengganu used CATs as one of the alternative treatment for various reasons. Majority of pregnant women used CATs after consulting with their health care provider.